The Climate and Hydrology of the Lake Balinsasayao Watershed, Negros Oriental, Philippines - Heideman, Paul D.; Erickson, Keith R. (Silliman Journal, 2024)
Climate variables were recorded and a water budget calculated for the Lake Balinsasayao catchment area, 302 ha of submontane forest surrounding a 76 ha lake 14 km west of Dumaguete City on Southern Negros Island. Mean annual temperature at the Lake was 22°C, 5.4°C cooler than Dumaguete City. Monthly rainfall at Lake Balinsasayao was highly correlated with that at 3100 - 300 mm, over 2.5 times that at Dumaguete City. Evaporation account for less than 15% of the 16,500 m3 of water lost daily from the lake. Since the lake has no surface outlet, the remaining 85% must be lost through seepage. Available evidence suggests that seepage from Lake Balinsasayao is the source of the springs that join to form the Colo River. Annual evapotranspiration at the lake was about 1700 mm, both during this study and according to data taken by others, July 1983- June 1984. Almost 75% of total rainfall on the forest was lost through evapotranspiration during the 1982-1983 study period; during the following twelve months, a wetter period, exapotranspirative losses were about 50% of total rainfall. Both annual evapotranspiration and percent runoff figures are higher than those recorded in most other studies on South-east Asian forest catchments. The result of this study suggests that development of the Lake area as either a hydroelectric power source or a tourist resort would prove unprofitable.